Human Dignity as a Constitutional Idea - Ali, Berez Abdullah (Journal of Legal and Political Studies, 2016)
As the human affects and is affected by what is happening around him, an outrage upon his dignity and feelings loses his identity of humanity. In order to avoid violations against human dignity, the state constitutions must guarantee and protect human dignity. For Germany, the first article of the Basic Law deals with protecting human dignity, and this article is not adjustable. As we can observe, the problem with this article is that instead of providing a specific and complete definition of human dignity, it gives an absolute and inclusiveness definition. Therefore, sometimes it depends on examples to define human dignity and clarify the frameworks of dignity. The German Federal Constitutional Court has own decisions to reject expansion of State control over the citizen's information, and can allow only within narrow limits that protect individual privacy, one can always easily say that increasingly stringent security measures and with the laws about to become a threat to the fundamental freedoms guaranteed by the Basic Law. Hence, the Federal Constitutional Court is rejecting numerous of decisions because they are unconstitutional laws and ensuring human dignity and violated the spirit and letter of the German Basic Law.
Keywords: dignity; identity of humanity; Federal Constitutional Court; German Basic Law